Perencanaan Desain Teknis Situs Megalitikum Gunung Padang Sebagai Objek Wisata Di Kab.Cianjur - Pranoto , Marimin Tri; Hernowo, Andre; Firdaus, Firman Syarif (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2017)
Megalithic site of Mount Padang is andent relics that have high value for Indonesia. The site is located 50 kilometers southwest Cianjur, West Java. The research objective was to determine the existence of the site, and planned as a tourism destination that may impact either directly or indirectly to the public. The method used is descriptive not only describe, but also perform the analysis and interpretation of data. The approach used in this study is qualitative. Cultural values that can be contained as various studies and are preferred for the sake of tourism. Conservation of cultural heritage sites as high an initiative of the stakeholders in maintaining, saving and utilizing high cultural value such as social capital and economic assets. The authors suggest that the megalithic site of Mount Padang is a megalithic sites that must be maintained existence. Therefore, the local government in collaboration with local communities are able to maintain and preserve the cultural heritage of the ancestors in order to still be able to enjoy the tourists in the future. In maintaining and rescue cultural heritage sites there should be continuous assessment of the methods and techniques of conservation of various artifacts that the values contained in it maintained its integrity. Methods and techniques that do besides using modern ways as well by utilizing indigenous knowledge usual local communities. In addition to improving the condition of conservation of the site will also be necessary rescue techniques assorted artifacts of the site, in the structuring, storage, and maintenance in order that the objects were well maintained